A positive feedback loop between RIP3 and JNK controls non‐alcoholic steatohepatitis. Issue 8 (24th June 2014) - Gautheron, Jérémie; Vucur, Mihael; Reisinger, Florian; Cardenas, David Vargas; Roderburg, Christoph; Koppe, Christiane; Kreggenwinkel, Karina; Schneider, Anne Theres; Bartneck, Matthias; Neumann, Ulf Peter; Canbay, Ali; Reeves, Helen Louise; et al.
Abstract Non‐alcoholic fatty liver disease (NAFLD) represents the most common liver disease in Western countries and often progresses to non‐alcoholic steatohepatitis (NASH) leading ultimately to liver fibrosis and liver cancer. The occurrence of hepatocyte cell death—so far characterized as hepatocyte apoptosis—represents a fundamental step from benign steatosis toward progressive steatohepatitis. In contrast, the function of RIP3‐dependent "necroptosis" in NASH and NASH‐induced fibrosis is currently unknown. We show that RIP3 is upregulated in human NASH and in a dietary mouse model of steatohepatitis. RIP3 mediates liver injury, inflammation, induction of hepatic progenitor cells/activated cholangiocytes, and liver fibrosis through a pathway suppressed by Caspase‐8. This function of RIP3 is mediated by a positive feedback loop involving activation of Jun‐(N)‐terminal Kinase (JNK). Furthermore, RIP3‐dependent JNK activation promotes the release of pro‐inflammatory mediators like MCP‐1, thereby attracting macrophages to the injured liver and further augmenting RIP3‐dependent signaling, cell death, and liver fibrosis. Thus, RIP3‐dependent necroptosis controls NASH‐induced liver fibrosis. This pathway might represent a novel and specific target for pharmacological strategies in patients with NASH.